WOMEN, FAMILY HEALTH AND WELL-BEING: NEED FOR STMcEDUCATION TO MEET ROLE EXPECTATIONS - Muhammad, Rabi (Sokoto Educational Review, 2020)
This paper discussed the position of women in the Nigerian Society. It highlighted the deprived underprivileged, marginalized and disadvantaged position of the Nigerian women. It also examine the role of women in family health and wellbeing considering their important role in the provision of good quality, adequate and safe food that meets the nutritional needs of each member of the family in order to avoid malnutrition which retards the growth of children physically, socially and mentally. It also looked at the role of Science Technology and Mathematics (STM) education in providing women with necessary knowledge, skills and attitude essential for safe motherhood and positive contribution to family health and wellbeing. It recommended that women should be given the best possible education to be able to perform their roles in the society as wives and mothers effectively.